Contemporary educational challenges: salesian education for innovation and participation in crisis context - Villagómez R., María Sol (2022)
The IUS Education Group (IUS EG) is an academic nenvork that belongs to the IUS Nenvork Today zz IUS, which are part of this Network" are distributed in America, Europe and Asia. Its mission is to streamline systematically and continuously the collaboration among Salesian Institutions of Higher Education that address the issue of education from both points of view of research and teaching as well as social projection or educational praxis.